Survey of Moving Target Defense in Power Grids: Design Principles, Tradeoffs, and Future Directions - Yexiang Chen; Charalambos Konstantinou; Daisuke Mashima; Anurag K. Srivastava; Subhash Lakshminarayana (IEEE Open Access Journal of Power and Energy, 2025)
Moving target defense (MTD) in power grids is an emerging defense technique that has gained prominence in the recent past. It aims to solve the long-standing problem of securing the power grid against stealthy attacks. The key idea behind MTD is to introduce periodic/event-triggered controlled changes to the power grid’s SCADA network/physical plant, thereby invalidating the knowledge attackers use for crafting stealthy attacks. In this paper, we provide a comprehensive overview of this topic and classify the different ways in which MTD is implemented in power grids. We further introduce the guiding principles behind the design of MTD, key performance metrics, and the associated trade-offs in MTD and identify the future development of MTD for power grid security.